Radikulopati Lumbal e.c. Herniasi Nukleus Pulposus (HNP) - Fitriyani; Aswan, Naufal Rasyid (Medula, 2024)
Radiculopathy is a disease involving the spinal nerve roots resulting from compression associated with the intervertebral discs; bone trauma; bone disease; and other conditions. Its prevalence is estimated to reach 3% -5% of the total population in the world. Age is the main risk factor, because it occurs due to degenerative processes in the spine. Men are often affected in their 40s while women are affected in their 50s and 60s. Clinical manifestations include radicular pain, weakness, and sensory loss referring to the structures innervated by the involved nerve root. The most common cause of lumbar radiculopathy is nerve root compression. Usually caused by disc herniation and spondylosis. This study aims to systematically assess patients diagnosed with lumbar radiculopathy. The method used is a Case Report with analysis of primary data obtained through anamnesis, physical examination and supporting examinations. It was reported that a female patient, aged 72 years, came to Dr. Hospital. H. Abdul Moeloek with complaints of pain in the back that radiates to both thighs, accompanied by numbness and weakness of the lower extremities. Denied history of trauma, history of hypertension, controlled with medication. On physical examination, he was aware of compos mentis and appeared to be in moderate pain, with vital signs and generalist status within normal limits. On neurological examination, he found decreased sensory and motor abilities in both thighs and positive results on the Lasegue sign examination. The supporting examination that was carried out was a lumbar MRI, which revealed diffuse posterior herniation of the nucleus pulposus L4-S1. Patients are given anti-pain and anti-hypertension therapy.